Kebijakan Bank Indonesia Dalam Menghadapi Krisis Keuangan - Ayu Sa’adah; Yuni Cahya Kurniasih; Putriana; Firman Maulana (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
The global financial crisis that occurred in 2008 had a significant impact on the Indonesian economy. To face these challenges, Bank Indonesia has implemented various monetary and macroprudential policies aimed at maintaining the stability of the financial system and national economy. These policies include adjusting benchmark interest rates, strengthening foreign exchange reserves, controlling inflation, and implementing macroprudential policies that focus on managing systemic risk.In an effort to maintain the stability of the rupiah exchange rate, Bank Indonesia has intervened in the foreign exchange market and increased foreign exchange reserves. Apart from that, Bank Indonesia also strives to keep inflation at a low and stable level through controlling liquidity and implementing appropriate monetary policy. To overcome systemic risks, Bank Indonesia has implemented macroprudential policies which include strengthening banking regulations, supervision of non-bank financial institutions, and increasing coordination with the government and related authorities.The success of Bank Indonesia's policies in dealing with the global financial crisis has helped maintain the stability of the Indonesian financial system and economy. However, new challenges continue to emerge, so Bank Indonesia needs to continue to make adjustments and evaluate policies on an ongoing basis to ensure financial system resilience and sustainable economic growth.